Unexpected one-pot formation of the 1H-6a,8a-epiminotricyclopenta[a,c,e][8]annulene system from cyclopentanone, ammonia and dimethyl fumarate. Synthesis of highly strained polycyclic nitroxide and EPR study - Dobrynin, Sergey A.; Kirilyuk, Igor A.; Gatilov, Yuri V.; Kuzhelev, Andrey A.; Krumkacheva, Olesya A.; Fedin, Matvey V.; Bowman, Michael K.; Bagryanskaya, Elena G. (Beilstein Journal of Organic Chemistry, 2019)
The unexpected formation of a highly strained polycyclic amine was observed in a one-pot synthesis from cyclopentanone, dimethyl fumarate and ammonium acetate. This multistep reaction includes 1,3-dipolar cycloaddition of dimethyl fumarate to the cyclic azomethine ylide formed in situ from cyclopentanone and ammonia. The polycyclic amine product was easily converted into a sterically shielded polycyclic nitroxide. The EPR spectra and spin relaxation behavior of the nitroxide were studied in solution. The spin relaxation seems well suited for the use as a biological spin label and are comparable with those of cyclic nitroxides with two spirocyclic moieties adjacent to the N–O· group.
Keywords: domino reactions; EPR; nitroxide; spin relaxation

Domino reactions: concepts for efficient organic synthesis - Tietze, L. F. (Wiley-VCH, 2014)

(untitled) - Hill, M. D. (Chem. – Eur. J., 2010)

(untitled) - Estévez, V.; Villacampa, M.; Menéndez, J. C. (Chem. Soc. Rev., 2014)

(untitled) - Dobrynin, S. A.; Glazachev, Y. I.; Gatilov, Y. V.; Chernyak, E. I.; Salnikov, G. E.; Kirilyuk, I. A. (J. Org. Chem., 2018)

(untitled) - Karthikeyan, G.; Bonucci, A.; Casano, G.; Gerbaud, G.; Abel, S.; Thomé, V.; Kodjabachian, L.; Magalon, A.; Guigliarelli, B.; Belle, V.; Ouari, O.; Mileo, E. (Angew. Chem., Int. Ed., 2018)

(untitled) - Bleicken, S.; Assafa, T. E.; Zhang, H.; Elsner, C.; Ritsch, I.; Pink, M.; Rajca, S.; Jeschke, G.; Rajca, A.; Bordignon, E. (ChemistryOpen, 2019)

(untitled) - Meyer, V.; Swanson, M. A.; Clouston, L. J.; Boratyński, P. J.; Stein, R. A.; Mchaourab, H. S.; Rajca, A.; Eaton, S. S.; Eaton, G. R. (Biophys. J., 2015)

(untitled) - Rajca, A.; Kathirvelu, V.; Roy, S. K.; Pink, M.; Rajca, S.; Sarkar, S.; Eaton, S. S.; Eaton, G. R. (Chem. – Eur. J., 2010)

(untitled) - Kathirvelu, V.; Smith, C.; Parks, C.; Mannan, M. A.; Miura, Y.; Takeshita, K.; Eaton, S. S.; Eaton, G. R. (Chem. Commun., 2009)

(untitled) - Kuzhelev, A. A.; Strizhakov, R. K.; Krumkacheva, O. A.; Polienko, Y. F.; Morozov, D. A.; Shevelev, G. Y.; Pyshnyi, D. V.; Kirilyuk, I. A.; Fedin, M. V.; Bagryanskaya, E. G. (J. Magn. Reson., 2016)

(untitled) - Edgar, O. B.; Johnson, D. H. (J. Chem. Soc., 1958)

(untitled) - Sen', V. D.; Golubev, V. A.; Efremova, N. N. (Russ. Chem. Bull., 1982)

(untitled) - Ali, S. A.; Wazeer, M. I. M. (Tetrahedron, 1993)

(untitled) - Biller, J. R.; Elajaili, H.; Meyer, V.; Rosen, G. M.; Eaton, S. S.; Eaton, G. R. (J. Magn. Reson., 2013)

(untitled) - Kirilyuk, I. A.; Polienko, Y. F.; Krumkacheva, O. A.; Strizhakov, R. K.; Gatilov, Y. V.; Grigor’ev, I. A.; Bagryanskaya, E. G. (J. Org. Chem., 2012)

(untitled) - Kirilina, E. P.; Dzuba, S. A.; Maryasov, A. G.; Tsvetkov, Y. D. (Appl. Magn. Reson., 2001)

(untitled) - Sato, H.; Kathirvelu, V.; Fielding, A.; Blinco, J. P.; Micallef, A. S.; Bottle, S. E.; Eaton, S. S.; Eaton, G. R. (Mol. Phys., 2007)

(untitled) - Stoll, S.; Schweiger, A. (J. Magn. Reson., 2006)